Impact of Board Incentives and Board Interlocks on Audit Fees - Elham Chenari (Iranian Journal of Accounting, Auditing & Finance)
This study aims to examine how board incentives and board interlocks affect audit fees. Using multiple linear regression with panel data, this research shows a significant relationship between the board incentives and future audit fees. In contrast, this relationship is not significant for current audit fees. Furthermore, there is a significant relationship between board interlock in companies with future audit fees, while this relationship is not significant for the current audit fees. This paper contributes to the literature on the determinants of audit fees.